Локализация неисправных подсхем в линейных и нелинейных схемах электронных устройств - Верлань, Анатолий Федорович; Положаенко, Сергей Анатолиевич; Дячук, Александр Анатолиевич (Kamianets-Podilskyi National Ivan Ohiienko University, 2017)
Diagnosing the operational state of electronic devices (ED) for various purposes is an important technical task. In the production plan and in the process of implementation, this task is significantly complicated by the need to obtain estimates of the state of the diagnosed object directly in the course of the operation of the ED. Especially relevant, this aspect of solving the diagnostic problem is for devices that are not subject to decommissioning. For example, this applies to alarm elements, non-redundant components of dispatch control, and to devices operating in the autonomous mode. The paper shows the possibility of practical application of the method of training and verification characteristics in problems of localization of faulty ECU sub-circuits both in the case of linear and nonlinear execution of the latter.